Evaluation of the efficiency and effectiveness of the accounting system of the Department of Missions and Cultural Relations (*) at the Office of the Ministry of Higher Education and Scientific Research - الجزراوي ابراهيم; بيرة ندى كاكي (Journal of Economics and Administrative Sciences, 2009)
The evaluation and efficiency and effectiveness of account system for the department of delegation and cultural Relationships in the center of ministry of higher Education and Scientific research Considered as a very important and active subjects in the modification of accounting system in this department and to develop it and make it able to make available important and accurate information for the planning requirements and monetary and evaluation performance and to make decisions, besides to develop the performance of Iraqi Cultural departments working abroad and to render its role effective to serve the students of higher education in the progressive Countries to facility its growing in scientific and professional and technical aspects by mixing the experiences and transfer it to Iraqi, and to achieve that, the two researchers depended on studying the actuality of accounting system in the delegations and cultural Relationships department and diagnosing the weak aspects and Recommendation to treat it for serving the research aims.